Helen Keller und die linguistische Aufhebung des aristotelischen „Anfangs“ - Gutberlet, L.C., Albert (Alpha Omega, 2020)
Summary: Philosophy in the Aristotelian sense may currently appear to have been replaced by the pragmatic sciences. But while today Aristotle’s justification of philosophy based on the “natural desire to know” seems insufficient, Helen Keller’s life and writings offer us a new ground for continuing in the Aristotelian Tradition: the “natural desire to communicate”, which “sublevates” or “takes up” the cognitive desire without discarding it. Key Words: Philosophy, science, Aristotle, Helen Keller, desire to communicate, cognitive desire. Sommario: La filosofia nel senso aristotelico potrebbe attualmente sembrare di essere stata sostituita dalle scienze prammatiche. Ma mentre oggi la giustificazione della filosofia data da Aristotele in base al “desiderio naturale di conoscere” appare insufficiente, la vita e gli scritti di Helen Keller ci offrono un nuovo fondamento per continuare nella tradizione aristotelica: il “desiderio naturale di comunicare”, che “solleva” il desiderio cognitivo senza scartarlo. Parole Chiave: filosofia, scienze, Aristotele, Helen Keller, desiderio di comunicare, desiderio cognitivo. <iframe class="ginger-extension-definitionpopup" style="left: -80.3472px; top: -103.785px; z-index: 100001; display: none;" src="chrome-extension://kdfieneakcjfaiglcfcgkidlkmlijjnh/content/popups/definitionPopup/index.html?title=Summary&description=a%20brief%20statement%20that%20presents%20the%20main%20points%20in%20a%20concise%20form">